(untitled) (Bangladesh Journal of Public Administration, 2021)
There has been a massive impact of global climate change on the environment that is already evident in various parts of the world. Bangladesh is heavily affected by different climate change issues, and riverbank erosion is one of them. Among others, women are the most vulnerable and suffer the most during the riverbank erosion in Bangladesh. Thus, the key focus of this paper was to understand the impact of riverbank erosion on the lives of women applying a qualitative research method. The objective of the paper was to understand the vulnerabilities and survival strategies of women living in riverbank erosion areas. Findings suggest that the impact of riverbank erosion on the lives of poor women is diverse. It creates a burden for the family members, and in most cases, they fall into a vicious circle of poverty. Despite the increased workload of women due to the unequal distribution of labor in the family, some women also experience a sense of empowerment with their engagement in various income-generating activities, decision-making process and increased physical mobility.